Self-esteem, academic performance and views on single parenting of adolescents from single-parent families. - Valencia, Ma. Jessica B.
The study sought to describe the self-esteem academic performance and views on single parenting of adolescents from single-parent families. Thirty (30) college students with ages 15 to 22 were conveniently sampled from different universities within Iloilo City. A Rosenberg Self-Estemm Scale was used to determine their level of self-esteem and their general weighted average was used to measure their academic performance. A questionnaire was developed to study their views on single parenting., It was found out that adolescents from single-parent families have high level of self-esteem. They are average performers in school. They viewed single parenting as a hard work which entails emotional and economic burden for both the single-parent and the children. From their own experiences, they observed that single parenting promotes greater cohesion among its family members.